Experienciando a avaliação da aprendizagem na Educação de Jovens e Adultos - Nascimento, Claudenice Maria Véras (2011)
This study aimed at understanding how learning assessment is experienced in the Education for Youth and Adults (EJA) program. It comprehensively approaches the way students, teachers, pedagogue, and coordinator in a public municipal school in Vitória, ES, Brazil experience learning assessment in the first segment of EJA, based on historical records of assessment in the world, in Brazil, in the state of Espírito Santo, and in the city of Vitoria, since the 19th century. The study adopted the phenomenological inspiration method, based on Heidegger’s Hermeneutics, open to qualitative study and a case study, all focusing on understanding the phenomenon in question and analytically obtaining the data. In order to gather data, official documents concerning learning assessment in EJA, observation of school routines, and testimonies were used. The interpretation and understanding built on the results obtained, allowed us to identify three units of meaning, named here: a) assessment as classification; b) assessment as domination practice: its “symbolic power”; and c) non-assessment masking non-teaching.